Pengaruh Sistem Reward, Work Life Balance, dan Self-Efficacy terhadap Kinerja Karyawan melalui Kepuasan Kerja pada PT Prodeco Wood Indonesia - Ayupuji Astutik; Qristin Violinda; Shofif Sobaruddin Akbar (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
This study examines the effects of the reward system, work-life balance, and self-efficacy on employee performance, with job satisfaction serving as a mediating variable among employees of PT Prodeco Wood Indonesia. A quantitative research design was employed using primary data collected through questionnaires measured on a five-point Likert scale. The population consisted of 118 employees, and 91 respondents were selected through simple random sampling. The data were analyzed using Partial Least Squares Structural Equation Modeling with SmartPLS 3, including validity and reliability assessments, R-square and F-square evaluation, and hypothesis testing through bootstrapping. The findings show that the reward system and work-life balance have positive and significant effects on employee performance, while self-efficacy has a positive but statistically insignificant direct effect. The reward system, work-life balance, and self-efficacy also have positive and significant effects on job satisfaction. Furthermore, job satisfaction positively and significantly influences employee performance. The mediation analysis confirms that job satisfaction mediates the effects of the reward system, work-life balance, and self-efficacy on employee performance. These results indicate that employee performance is shaped not only by organizational policies and individual confidence, but also by the extent to which employees experience satisfaction in their work. Therefore, PT Prodeco Wood Indonesia should strengthen fair reward practices, support a healthier balance between work and personal life, and create conditions that reinforce employee confidence and job satisfaction to achieve sustainable performance improvement.